Characterization and treatment of brain metastases from pancreatic cancer: a systematic review - Yuanchi Ma; Hairong He; Boyang Li; Weiqi Lyu; Weikun Qian; Liang Han; Zheng Wang; Kongyuan Wei (Discover Oncology)
Abstract Background Brain metastases (BM) from pancreatic cancer have low incidence, carry a poor prognosis, and have limited treatment options. Summarizing disease features and treatment protocols can help understand and improve prognosis. Methods Registered with INPLASY and following PRISMA guidelines, the study searched PubMed, Embase, Scopus, and Web of Science from database inception to 9th January 2025. The Kaplan–Meier method was used to calculate the median survival time and interquartile range (IQR) of Overall Survival (OS), and the corresponding plot was drawn. Results A total of 614 patients with BM from pancreatic cancer were included, originating from 24 case reports & series and 3 retrospective cohort studies. BM was usually multiple (n = 32, 71.1%), and mostly affecting frontal lobes (n = 30, 23.8%). Radiotherapy was primary treatment for BM in both pancreatic surgical (n = 44, 72.1%) and non-surgical (n = 8, 66.7%) groups, and most patients in the non-surgical group underwent chemotherapy and targeted therapy (41.7% vs 6.6%). Patients who underwent pancreatic surgery, had longer time from diagnosis of pancreatic cancer to BM (median: 24.0 vs 11.9 months) but shorter post-BM survival [median: 6.0 (case report/series), 3.0 (retrospective cohort study) vs 10.0 months]. Conclusion This review covers the characteristics, treatment, and prognosis of patients with BM from pancreatic cancer. Radiotherapy may be considered the primary treatment for BM, and pancreatic surgery may impact treatment and prognosis. Large multicenter studies are needed in view of low BM incidence from pancreatic cancer.